The Analysis of Corporate Taxpayer Compliance and Its Implication to Self-Assessment System Implementation: (Case Study of Tax Officer Pratama Bandung Karees) - Purwanto Purwanto; Hasna Safira (Yayasan Riset dan Pengembangan Intelektual, 2020)
Self-Assessment System will run effectively if the law implementation such as auditing the taxpayers and enforcing the tax sanction are done optimally. This study aims to examine the impact of tax audit and tax sanctions on corporate taxpayer’s compliance and its implication to Self-Assessment System implementation in Tax Officer Bandung Karees. The technique of data collection and sampling was done purposively by using questionnaires on Google Form and 110 respondents were obtained. The analysis method used was path analysis. The result showed that both tax audit and tax sanction had a significant effect on corporate taxpayer’s compliance by 60.10% and the remaining 39.90% was influenced by other variables. Tax audition had a direct relationship with Self-Assessment System implementation, while tax sanction has an indirect relationship with the implementation of Self-Assessment System, with corporate taxpayer’s compliance variable as an intervening variable. If both independent variables are consistently conducted, there will be a significant impact to Corporate Taxpayer Compliance, so that the tax revenue target can be achieved as soon as possible. Keywords: Corporate Taxpayer Compliance, Self-Assessment System, Tax Audit, Tax Sanction